Studies on Human Factor VIII and its Antibodies Using Radiolabelling and Affinity Chromatography - Kavanagh, M L; Wood, C N; Davidson, J F (Thrombosis and Haemostasis, 1981)
An immuno-affinity chromatography method was used to isolate human factor VIII and its antibodies and the mechanism of the affinity system was investigated using iodine labelling.Rabbit antibodies to human factor VIII were insolubilised onto CNBr — activated Sepharose 2B which was used for the preparation of affinity columns. Both VIII:C and VIIIR:Ag were adsorbed onto such columns from factor VIII preparations. The subsequent application of immunoglobulin preparations containing human antibodies to factor VIII resulted in the adsorption of these antibodies onto the columns. Adsorbed material was eluted from the affinity columns with 0.2 M glycine - HCl, pH 2.3.When 125I-labelled factor VIII and 131I-labelled human antibodies to factor VIII were used in this affinity system, the eluted material could be separated into three fractions by gel filtration on Bio-Gel A 1.5 m. Fraction 1 occurred at the void volume position, fraction 3 at a position corresponding to the elution position of IgG and fraction 2 at an intermediate position. 131I-labelled material was present in all three peaks. 125I-labelled material was present mainly in peak 1, with a little in peak 2. The results support the view that VIIIR: Ag, which binds heterologous antibodies, is non-covalently linked to a smaller subunit, VIII.C, which binds homologous antibodies.
Keywords: Factor VIII; Radiolabelled factor VIII; Radiolabelled antibodies to factor VIII